Winning hearts and minds British governments, the media and colonial counter-insurgency 1944 - 1960 - Carruthers, Susan L. 1967- (Leicester Univ. Press, 1995)
"Over the fast twenty-five years, terrorism has attracted immense public and governmental interest. It is not, however, a new phenomenon. This study examines how post-war colonial insurgencies in Palestine, Malaya, Kenya and Cyprus were regarded by British policy-makers and the military as the 'terrorism' of their day. Using a great array of archive material, including mass-media sources, the author analyses the way in which propaganda formed an integral part of counter-insurgency strategy. Not only did British governments and their colonial officials produce their own publicity material on events in troubled colonies, they also sought to shape how the media - in Britain and elsewhere - reported them. Unlike many studies of colonial insurgency, this book examines both domestic and international aspects of the battle for 'hearts and minds'."--BOOK JACKET.